Dekonstruksi Stereotip Gender Dalam Iklan “Kebahagiaan Kecil” Gopay Indonesia - Octaviana, Rizka; Mustiawan, Mustiawan; Setiawati, Titin (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2024)
AbstractThis study aims to analyze the deconstruction of gender stereotypes in GoPay Indonesia's